Peran Mediasi Inklusi Keuangan pada Pengaruh Literasi Keuangan dan Teknologi Keuangan terhadap Keberlanjutan Usaha Menengah di Kabupaten Buleleng - Suardana, Komang Yudi; Purnamawati, I Gusti Ayu; Werastuti, Desak Nyoman Sri (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
This study aims to empirically prove the influence of financial literacy and financial technology on the financial inclusion of medium-sized businesses in Buleleng Regency, the influence of financial literacy, financial technology, and financial inclusion on the sustainability of medium-sized businesses in Buleleng Regency, and the influence of financial literacy and financial technology on the sustainability of medium- sized businesses in Buleleng Regency through financial inclusion. The population in this study consisted of medium-sized businesses in Buleleng Regency, totaling 1,327 units. The minimum sample size was calculated using the Slovin formula with a significance level of 5%, so a sample of 308 medium-sized businesses was obtained. The sample was selected using a purposive sampling technique. Data analysis used SEM-PLS assisted by SmartPLS Version 3 software. The results showed that financial literacy and financial technology positively affected financial inclusion. Financial literacy, financial technology, and financial inclusion positively affected business sustainability. Financial literacy and financial technology positively affected business sustainability through financial inclusion. Financial technology is a variable that has a dominant influence on business financial inclusion. Financial inclusion is a variable that has a dominant influence on business sustainability.